Entangled Entertainers Jews and Popular Culture in Fin-de-Siècle Vienna - Hödl, Klaus (Berghahn Books, 2019)
With a particular focus on vaudeville singers and artists, this book examines the role that Viennese Jews played in the city's rich popular culture around 1900. Through a series of extensively researched case studies, it shows that-notwithstanding the real phenomenon of antisemitism in Viennese culture--there was substantial and diverse cooperation between Jews and Gentiles, and that their private relations were also very close. The many and diverse contacts and linkages between these two populations in popular culture powerfully shaped both the experience and the popular understanding of Jewish identity.